VD_FINDINFO Jug / 2015 / 449 vom 11. Juni 2015 - VD Tribunal cantonal (2015)
INJURE, CONTRAINTEDROIT PÉNAL, INSOUMISSION À UNE DÉCISION DE L'AUTORITÉ, AMENDE | 106 CP, 150 CP, 177 al. 2 CP, 177 CP, 181 CP, 34 CP, 42 CP, 44 CP, 47 CP, 49 al. 1 CP